Geographies of race and food fields, bodies, markets - Slocum, Rachel B. 1964-; Saldanha, Arun (Critical food studies, 2013)
"While interest in the relations of power and identity in food explodes, a hesitancy remains about calling these racial. What difference does race make in the fields where food is grown, the places it is sold and the manner in which it is eaten? How do we understand farming and provisioning, tasting and picking, eating and being eaten, hunger and gardening better by paying attention to race? This collection argues there is an unacknowledged racial dimension to the production and consumption of food under globalization. Building on case studies from across the world, it advances the conceptualization of race by emphasizing embodiment, circulation and materiality, while adding to food advocacy an antiracist perspective it often lacks. Within the three socio-physical spatialities of food - fields, bodies and markets - the collection reveals how race and food are intricately linked. An international and multidisciplinary team of scholars complements each other to shed light on how human groups become entrenched in myriad hierarchies through food, at scales from the dining room and market stall to the slave trade and empire. Following foodways as they constitute racial formations in often surprising ways, the chapters achieve a novel approach to the process of race as one that cannot be reduced to biology, culture or capitalism."--Publisher.